1988
DOI: 10.1017/s0007485300013110
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype variation in the corn leaf aphid, Rhopalosiphum maidis (Fitch), species complex (Hemiptera: Aphididae) in relation to host-plant and morphology

Abstract: Rhopalosiphum maidis (Fitch) collected on barley in the northern hemisphere usually has a ten-chromosome karyotype, whereas samples from maize, sorghum and Johnson grass (Sorghum halepense) from all parts of the world commonly have 2n = 8. Samples with other karyotypes (2n = 9, 2n = 11 and 2n = 8 heterozygous for an interchange between the X chromosomes) occur less frequently on these and other species of Gramineae. Multivariate morphometric analysis, principally by the method of canonical variates, indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 4 publications
4
51
0
Order By: Relevance
“…In phytophagous insects, host plant shifting might be an important factor in sympatric divergence and speciation (Berlocher & Feder, 2002;Horn et al, 2006;Loxdale, 2010). In some aphids, another group of the order Hemiptera, polymorphism for chromosome number was found to be correlated with change of host plants (Brown & Blackman, 1988;De Barro et al, 1995;Hales et al, 2000). Such karyotypic divergence in relation to host plant is known to occur in the genus Amphorophora where A. idaei Börner, which feeds on raspberry (Rubus idaeus) has 2n = 18, whereas A. rubi (Kaltenbach), which feeds on blackberry (Rubus fruticosus agg.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phytophagous insects, host plant shifting might be an important factor in sympatric divergence and speciation (Berlocher & Feder, 2002;Horn et al, 2006;Loxdale, 2010). In some aphids, another group of the order Hemiptera, polymorphism for chromosome number was found to be correlated with change of host plants (Brown & Blackman, 1988;De Barro et al, 1995;Hales et al, 2000). Such karyotypic divergence in relation to host plant is known to occur in the genus Amphorophora where A. idaei Börner, which feeds on raspberry (Rubus idaeus) has 2n = 18, whereas A. rubi (Kaltenbach), which feeds on blackberry (Rubus fruticosus agg.)…”
Section: Discussionmentioning
confidence: 99%
“…In this species there is a strong association between chromosome number and host plant. Specimens with 2n = 8 are found on Sorghum and Zea mays, whereas on northern hemisphere barley, Hordeum vulgare, 2n = 10 is common (Brown & Blackman, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In this species 2n=8 is associated with samples from maize, sorghum and Johnson grass, whereas 2n=10 is associated with barley (Brown and Blackman 1988). Earlier, Chattopadhay et al (1982) also observed differences in number and size of chromosomes in samples of R. maidis (2n=8 and 10) collected from Triticum vulgare and Zea mays respectively.…”
Section: Discussionmentioning
confidence: 71%
“…The relationship between karyotype variation and association with host plant has been reported in Rhopalosiphum maidis (Brown and Blackman 1988). In this species 2n=8 is associated with samples from maize, sorghum and Johnson grass, whereas 2n=10 is associated with barley (Brown and Blackman 1988).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation